Research on the Influence of Shanghai Import Trade Structure on Technological Progress - Guoe, Xie; Jia, Yu (Advances in Social Sciences Research Journal, 2021)
Based on the statistical data from 1995 to 2018, this paper uses regression analysis, error correction model and impulse response analysis to empirically test the specific impact of import trade structure on Shanghai's technological progress. The results show that the decrease in the proportion of intermediate goods imports promotes the technological progress, while the increase in the proportion of capital goods imports has a significant positive impact on Shanghai's technological progress. The relationship between FDI and technological progress in Shanghai is negative. The development of Finance and the increase of patent authorization promote the technological progress of Shanghai. The stability test of VEC model shows that there is a long-term equilibrium and stable relationship among the variables. Impulse response analysis shows that there is a bidirectional interaction between the import trade structure and Shanghai's technological progress. Therefore, we should further reduce the quantity of intermediate goods with low technology content and increase the import volume of capital goods appropriately. At the same time, we should attach importance to innovation based on introduction and absorption, and use the platform of China International Import Expo to attract foreign enterprises to widely display new products, new technologies and new services of various countries, so as to help high-quality development in the future.